The Main Pathways For Improving Educational Quality In ‎State Islamic Senior High Schools in Deli Serdang Regency: An ‎Analysis of Principals' Policies, Personality Traits, and ‎Professional Development - Habibi Habibi; Mesiono; Masganti Sitorus (JPI: Jurnal Pustaka Indonesia, 2026)
This study aimed to examine the direct effects of principal policy practices, teachers’ Big Five personality traits, and teacher professional development on perceived educational quality and to assess the potential mediating role of professional development in state Islamic senior high schools. A quantitative cross-sectional census survey was conducted involving 97 teachers from two State Islamic Senior High Schools in Deli Serdang Regency, Indonesia, between December 2025 and March 2026. Data were collected using five-point Likert-scale questionnaires and analyzed through two-equation path analysis using IBM SPSS. The diagnostic tests indicated acceptable residual normality, tolerance values ranging from .237 to .780, variance inflation factors ranging from 1.282 to 4.220, and no systematic heteroscedasticity. Principal policy practices (β = .612, t = 4.283), Big Five personality traits (β = .694, t = 3.936), and teacher professional development (β = .785, t = 4.449) were positively associated with perceived educational quality (all p < .001). Principal policy practices (β = .514, t = 3.535) and Big Five personality traits (β = .530, t = 4.158) were also positively associated with professional development (both p < .001). The estimated indirect effects were .403 and .416, although their statistical significance could not be established without bootstrap confidence intervals. The findings indicate that educational quality improvement requires the integration of transparent, instructionally focused school policies and continuous, collaborative, and differentiated professional development. However, the cross-sectional design, limited institutional setting, and absence of bootstrapped mediation tests restrict causal interpretation and generalizability. Future studies should employ longitudinal, multisite designs and bootstrap-based mediation analysis.